Korelasi Keharmonisan Hubungan Sosial antar Guru dengan Kinerja Guru di SMA Negeri 8 Pekanbaru - Kurnia, Desi; Syafaruddin, Syafaruddin; Setyaningsih, Rini (Universitas Persatuan Guru 1945 NTT, 2020)
It was a correlational research studying about social relationship harmonization among teachers (X) and teacher performance (Y) at State Senior High School 8 Pekanbaru. This research aimed at knowing teacher performance level, social relationship harmonization level among teachers, and the correlation between both variables. All teachers that were 83 teachers were the population of this research. Questionnaire and documentation were the techniques of collecting the data. The data were analyzed by using Pearson Product Moment correlation formula. Based on the analysis results, it showed that H0 was rejected and Ha was accepted. It meant that there was a positive significant correlation between social relationship harmonization among teachers and teacher performance at State Senior High School 8 Pekanbaru. It could be seen from the difference between robserved 0.409 and rtable 0.2159 at 5% significant level with N=83, so robserved was higher than rtable (0.409>02159). Based on the data results of the coefficient of linear regression, it showed that the probability score or the significant score 0.000 was lower than 0.05 (0.000<0.05). Based on the coefficient of determination, it was obtained the score that was 0.167 or 16.7%, and it was merged into 17%. It meant that the contribution of the variable of social relationship harmonization among teachers toward the variable of teacher performance at State Senior High School 8 Pekanbaru was 17%, and the rest was influenced by other variables. So, it was needed to build the harmonic social relationship among teachers to increase teacher performance.